2016
DOI: 10.1080/10773525.2016.1247026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of occupational injury and its contributing factors among rubber tappers in Galle, Sri Lanka

Abstract: Background: Rubber tapping involves carrying heavy loads, navigating rough terrain, and using sharp tools. However, little is known about occupational injury among this vulnerable working population. Objective: To assesses the prevalence, severity, and contributing factors associated with occupational injury among Sri Lankan rubber tappers and to identify possible interventions to improve occupational safety. Methods: A questionnaire was administered to 300 Sri Lankan rubber tappers. The associations between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…There were 3 studies that focused on psychosocial risk factors, such as lack of control and high demands, and their association with health [ 26 , 32 , 39 ]. Some studies investigated the lack of knowledge and awareness of occupational safety and health risks on the part of workers and employers [ 16 , 17 , 20 , 30 ] and poor safety practices such as the non-completion of safety training and non-use of personal protective equipment at work [ 17 , 20 , 25 , 29 , 36 ]. These are actions at the micro level that can help identify and mitigate occupational exposures, hazards, and risk factors in the workplaces.…”
Section: Resultsmentioning
confidence: 99%
“…There were 3 studies that focused on psychosocial risk factors, such as lack of control and high demands, and their association with health [ 26 , 32 , 39 ]. Some studies investigated the lack of knowledge and awareness of occupational safety and health risks on the part of workers and employers [ 16 , 17 , 20 , 30 ] and poor safety practices such as the non-completion of safety training and non-use of personal protective equipment at work [ 17 , 20 , 25 , 29 , 36 ]. These are actions at the micro level that can help identify and mitigate occupational exposures, hazards, and risk factors in the workplaces.…”
Section: Resultsmentioning
confidence: 99%
“…The present study findings were in line with a study among rubber tappers in Sri Lanka, where 65% of participants reported MSS in the last 12 months, and the low back (43%) was the most affected region. 23 Another study conducted among rubber tappers in Thailand reported that 53% of the respondents had low back pain during the previous three months. 24 A study conducted among tea leaf pluckers in Tamil Nadu, India, reported that MSS in the last 12 months were 83.6%, and the most affected body region was the shoulders (59%).…”
Section: Discussionmentioning
confidence: 99%
“…A study on prevalence of work-related eye injuries among rubber tappers in Sri Lanka quotes ocular injuries as the second major work-related injury and only 58% took (5) consultation for it . The study also states poor vision as an important barrier the rubber tappers face.…”
Section: Dr Biju Gopalmentioning
confidence: 99%
“…Good vision is crucial to this group to prevent injuring themselves. Almost 26% of study participants reported poor vision as a barrier to (5) their efficiency . As age increases, vision may become worse, exacerbating this issue.…”
Section: Dr Biju Gopalmentioning
confidence: 99%
See 1 more Smart Citation